Epidemiological aspects of viral hepatitis - Passos, Afonso Dinis Costa (Medicina (Ribeirao Preto), 2003)
Some of the main epidemiological characteristics of the five identified types of viral hepatitis are presented, emphasizing those caused by virus B and C. These two forms show a large geographical distribution and ability to cause chronic infections, which are associated with cirrhosis and liver cancer. Thus, these forms of hepatitis are an important public health problem worldwide. Their epidemiological relevance and main transmission routes are discussed.